A case study of Twitter as a research tool - Corbett, B.; Edwards, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
This paper documents the process of utilizing Twitter for a doctoral dissertation in rugby governance, and highlights the key benefits of using Twitter as a research tool. Research followed a case study approach to delve into the four major uses of Twitter: (1) a warning system for dramas or incidents relating to one`s research field; (2) data collection; (3) finding and recruiting research subjects; and (4) building a personal research brand. The research design used a mixed method approach that combined qualitative and quantitative analysis methods. The findings serve as the basis for the pursuit of more detailed future research with Twitter as the principal medium in focus within the area of sport.